MEMBANGUN KESADARAN SOSIAL MAHASISWA STAI DARUL FALAH MELALUI PARTISIPASI DALAM KEGIATAN BAKTI SOSIAL DONOR DARAH - Ayu Puji Rahayu; Fikri Rizkia Muhammad; Mohammad Sabarudin; Murharyana Murharyana (Jurnal Al Maesarah, 2023)
Community service activities (PkM) in the KKN program can be used as a vehicle for the application and development of knowledge outside the campus. Through the voluntary blood donor social service program, it is hoped will increase the social awareness of STAI Darul Falah students about public health problems. The activity with the theme "A Drop of Your Blood, Hope for Others", is a strategy that can foster knowledge and practical experience in the field. So that students understand the benefits of blood donation not only textually but also contextually as one of the problems found in people's lives. The experience of working together in teams from various elements of society has increased the ability of students to take part in the community both disciplinary and interdisciplinary. This can hone their soft skills in building social networks. So that they are better prepared to be part of a productive and efficient society. Keywords: Social Awareness, Students, Blood Donation, Community Service